(untitled) (Paliativní medicína, 2023)
The article conceptually defines the differences between spiritual bypass, coping, and emergence concerning afterlife belief. The concepts are explored regarding to spirituality manifestations, impacts, and characteristics. I used typology defined by Jaakkola as methodological tool for the paper. Possible recommendations for professional support for the bereaved are drawn from the typology.